THE DIFFERENCES OF CHRONOLOGICAL AGE WITH DENTAL AGE BASED ON THE ALQAHTANI METHOD AGED 6-12 YEARS - Mutiara Sukma Suntana; Ira Artilia; Lucy Pertiwi (Fakultas Kedokteran Gigi Unjani, 2021)
The chronological age of a person can not provide sufficient information. We can use the dental age in panoramic radiographs to know the growth process appropriately compared to The London Atlas of the Alqahtani method. Children aged 6-12 years have various factors that can affect the velocity in tooth growth and development, such as male and female. This study aims to determine the chronological patient's age differences with dental age based on the Alqahtani method on a panoramic radiograph at Unjani Dental and Oral Education Hospital. This type of research is Analytical Observational with the Cross- Sectional Study method. Research subjects were obtained from all medical records panoramic radiographs with 72 panoramic radiographs aged 6-12 years, divided into 36 male patients and 36 female patients. Differences in chronological age with dental age were analyzed statistically using the Mann-Whitney test and Wilcoxon test, previously tested for the normality using Kolmogorov-Smirnov. The results showed a significant difference between chronological age and dental age by gender and in all patients at the Unjani Dental and Oral Education Hospital (p<0,05). Based on the analysis of the data obtained, all patients in RSGMP Unjani aged 6-12 years have different dental developmental growth processes, and the dental development growth of female patients was faster than male patients. It can be concluded that the dental age is not always comparable with chronological age because of various factors such as gender, genetics and environment, which can affect the dental age. DOI : 10.54052/jhds.v1n1.p60-70